Cognitive consequences of business shut down. The case of Ugandan repeat entrepreneurs - Sserwanga, Arthur; Rooks, Gerrit (International Journal of Entrepreneurial Behavior & Research, 2014)
The purpose of this paper is to focus on the cognitive and motivational consequences of a business failure, and their relation with subsequent start up success. The paper hypothesizes that if previous business failure was attributed to an internal and stable cause, subsequent business would be less successful compared to where an entrepreneur attributed business failure to an internal and unstable cause. Design/methodology/approach – The authors reviewed the literature on attribution theory in an achievement context and derived a hypothesis about the relation between causal thinking and subsequent business success. A survey amongst entrepreneurs in Uganda was carried out to yield insights on how attributions to past performance influence subsequent business performance. Findings – Entrepreneurs who attributed previous business failure to an internal, stable cause were found to be less successful in subsequent business start up. When repeat entrepreneurs attribute previous shut down to a lack of ability, they are less successful in a subsequent business start up. However, attributing the failure to a lack of effort, does not affect subsequent business success. Originality/value – The study reaffirms the importance of attributional thinking in entrepreneurship and provides empirical evidence on the relationship between the way entrepreneurs think about their previous performance and subsequent performance. Attributional thinking influences subsequent business actions and outcomes, which offers important practical applications. For instance training to change attributions of entrepreneurs may be used to influence their eventual performance.
Keywords: Entrepreneurship; Attribution theory; Business success; Cognitive perspective; Repeat entrepreneurs